POSITIVE PSYCHOLOGY: PERSONALITIES, MAJOR ISSUES, ADVANTAGES AND DISADVANTAGES - Dian Febrianingsih; Moh. Toriqul Chaer (Universitas Muhammadiyah Ponorogo, 2018)
Since the beginning of the emergence of Psychology flow (the flow of behaviourism), seen as a man filled with mechanical problems. This flow then sees the problem that exists in humans, not to mention with the view of psychoanalysis who viewed the memories of the past as the cause of suffering that exists today. That's why psychology that deals with the problem often referred to as negative psychology, because in its more to the negative side of human pathological. Psychology meant only limited offer of therapy over psychiatric problems. In fact, humans do not just want to be free of the problem, but also crave happiness. Martin Seligman, a psychologist expert study of optimism, pioneered a revolution in psychology through the positive psychology movement. Positive psychology positive emotions associated with the excavation, such as happy, kindness, humour, love, optimistic, kind, and so on. Positive psychology is not intended to replace or eliminate suffering, disadvantage or disruption (soul), but rather to add to the Treasury or to enrich, as well as to understand scientifically about the human experience.